Developing a new technology for demonstrating environmental sustainability in the Australian grassfed beef industry - Sarwar, Salman; Ross, Helen; van Bommel, Séverine; Polack, Sharelle; Waschka, Marie; Lubcke, Katelyn; Bryceson, Kim; Cooper, Tarni L.; Butler, Don W.; Macintosh, Andrew (Frontiers in Sustainable Food Systems, 2023)
Meeting the increasing consumer and market expectations for sustainably produced beef requires measurement and demonstration of the producers’ sustainability practices. Typically, demonstration of sustainable production relies on time consuming and costly on-ground audits. Online tools using combinations of remotely sensed data and other information sources could offer a cost-effective alternative. However, there are also concerns about the merits and risks of such tools. This paper presents a case of the development process of an online platform for Australian beef producers to demonstrate their sustainable production practices, connected with learning opportunities for continual improvement of their sustainability performance. The project is led by an innovative cross-sectoral collaboration of beef industry, non-government organisation and university partners. Our approach combines producer and market perspectives; focusing on the “value proposition” of the proposed technology for producers, and value chains’ priorities in sustainability markets and in having the ability to demonstrate sustainability in a cost-effective manner. The development process adopted co-design at three levels: (1) the “Consortium” of project partners (2) collaborative co-design through small online groups with producers and value chain representatives; and (3) consultative co-design through producer testing of the platform as it is built by software developers. The design process focused on five themes: tree cover, ground cover, biodiversity stewardship, carbon balance, and drought resilience. We present the main platform design characteristics sought by the co-design groups, and the indicators and measures they considered important for each of the five themes. We then discuss a set of key issues and their implications for technology development, according to a framework expressing interactions between people and their properties, processes and technology. This case shows the importance of taking a “demand-led” rather than a “supply-driven” approach, for the best possible fit of new technology to its users. Since co-design is more often consultative than treating users as equals or leaders in a technology design process, our case highlights the desirability of a fully collaborative approach to co-design.